Redefining n-th order limit languages in extended-H splicing system - Siti Hajar, Mohd Khairuddin; Muhammad Azrin, Ahmad; Mohd Sham, Mohamad; Rajalingam, Sokkalingam (World Scientific and Engineering Academy and Society, 2025)
This research delves into the fascinating intersection of formal language theory and molecular biology by examining DNA splicing systems. DNA splicing is a process of rearranging genetic material by cutting and rejoining DNA strands. Researchers have developed computational models inspired by these mechanisms, which are splicing systems that allow for simulation and analysis of the process of cutting and pasting DNA to produce new strands. This study builds upon prior research that defined the n-th order limit language, a concept initially introduced by Goode and Pixton and subsequently refined by defining based on rules perspectives. While originally rooted in the biological characteristics of DNA splicing, this concept is now being re-examined within the framework of the Păun splicing system. This shift in focus moves away from purely biological models and embraces language generation processes, aligning with the well-established Chomsky hierarchy. By redefining the n-th order limit language in this context, the research seeks to strengthen the theoretical foundation and expand the practical applications of DNA splicing systems in formal language theory.